Assessment of digital competencies in higher education students: development and validation of a measurement scale - Mejías-Acosta, Agustín; D'Armas Regnault, Mayra; Vargas-Cano, Eduardo; Cárdenas-Cobo, Jesennia; Vidal-Silva, Cristian (Frontiers in Education, 2024)
Digital competencies represent students' ability to use technology and digital media interactively to enhance their learning experiences. Given their growing importance, there is a need to develop instruments that can be used in different contexts to measure them. This research aims to develop and validate an instrument to measure digital competencies in university students and identify the dimensions that characterize it. Based on a literature review, a scale is designed and validated with students from a Venezuelan university. As a result, a model of 22 variables grouped into four dimensions is presented: Communication and digital security, Access to digital content management, Creation of digital content and use of digital media, and Digital empathy, which can be applied in similar environments. The results of the tests demonstrate the scale's psychometric properties in terms of both validity and reliability.